2014
DOI: 10.4161/21565562.2014.979103
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of estrogen receptor signaling and similar pathways in the efferent ductules and initial segment of the epididymis

Abstract: Seminiferous tubular atrophy may involve indirectly the disruption of estrogen receptor-a (ESR1) function in efferent ductules of the testis. ESR1 helps to maintain fluid resorption by the ductal epithelium and the inhibition or stimulation of this activity in rodent species will lead to fluid accumulation in the lumen. If not resolved, the abnormal buildup of fluid in the head of the epididymis and efferent ductules becomes a serious problem for the testis, as it leads to an increase in testis weight, tubular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 238 publications
1
33
0
Order By: Relevance
“…Scale bar = 50 μm. AA, ascorbic acid isoprenylation in theca-interstitial cell culture (Ortega et al, 2012;2014). Contrary to this, AA is able to increase androgen production by augmenting luteinizing hormone receptors expression in Leydig cells and stimulating steroidogenic enzymes 3β-hydroxysteroid dehydrogenase, 17β-hydroxysteroid dehydrogenase and StAR protein in the testis (Harikrishnan et al, 2013;Radhakrishnakartha, Appu, & Indira, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Scale bar = 50 μm. AA, ascorbic acid isoprenylation in theca-interstitial cell culture (Ortega et al, 2012;2014). Contrary to this, AA is able to increase androgen production by augmenting luteinizing hormone receptors expression in Leydig cells and stimulating steroidogenic enzymes 3β-hydroxysteroid dehydrogenase, 17β-hydroxysteroid dehydrogenase and StAR protein in the testis (Harikrishnan et al, 2013;Radhakrishnakartha, Appu, & Indira, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Estrogens mainly play their role through binding to their cytoplasmic receptors (ERS1 or ERS2) forming hormone-receptor complexes that are translocated to the nucleus, where they modulate gene expression (Carreau et al, 2011). Previous studies have demonstrated that ERS1 knockout mice show infertility at adulthood (Shibayama et al, 2001) and fluid accumulation in the testis, an abnormal concentration of sperm and compromised sperm maturation in the caput of epididymis (Hess, 2014). Furthermore, a decreased ERS1 expression is also related to increased sperm abnormalities, decreased sperm motility (Couse & Korach, 1999;Guerra et al, 2016) and reduced sperm counts (Couse & Korach, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the stirring or mixing function of efferent ductule cilia is essential for homogenous reabsorption of fluid by the nonciliated cells, as previously predicted. [45][46][47] Additionally we speculate that the near absence of sperm from the epididymis could be caused by impaired fluid flow, an occlusion or a defect in smooth muscle contraction, which may rely upon signaling from the efferent ducts. Irrespective of the contribution of the multiciliogenesis defect, we believe that the primary problem is an accumulation of luminal fluid that reflects both impaired absorption and excess secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The main source of estrogen in males is the testis; however, the additional presence of P450 aromatase in spermatozoa provides a local source of estrogen in the epididymis (Reviewed in Hess 2014). As the estrogen action in the epididymis was recently reviewed (Hess et al 2011, Hess 2014, this review will focus on androgen regulation. Of note, however, is the notion that the correct balance between androgen and estrogen levels might be of importance for maintaining epididymal functions.…”
Section: Regulation Via Steroid Hormonesmentioning
confidence: 99%
“…Inside the epididymal epithelial cells, testosterone is reduced to more potent dihydrotestosterone (DHT) by 5α-reductases (Robaire & Hamzeh 2011). The main source of estrogen in males is the testis; however, the additional presence of P450 aromatase in spermatozoa provides a local source of estrogen in the epididymis (Reviewed in Hess 2014). As the estrogen action in the epididymis was recently reviewed (Hess et al 2011, Hess 2014, this review will focus on androgen regulation.…”
Section: Regulation Via Steroid Hormonesmentioning
confidence: 99%